2018
DOI: 10.1016/j.celrep.2018.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genomic Crosstalk between Glucocorticoid Receptor and Estrogen Receptor α In Endometrial Cancer

Abstract: SUMMARY Steroid hormone receptors are simultaneously active in many tissues and are capable of altering each other’s function. Estrogen receptor α (ER) and glucocorticoid receptor (GR) are expressed in the uterus, and their ligands have opposing effects on uterine growth. In endometrial tumors with high ER expression, we surprisingly found that expression of GR is associated with poor prognosis. Dexamethasone reduced normal uterine growth in vivo; however, this growth inhibition was abolished in estrogen-induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Indeed, blocking dynorphin action with a kappaopioid receptor antagonist elicits an increase in LH pulse frequency [23,47] which is associated with increased multi-unit activity in the mediobasal hypothalamus [23]. We evaluated dynorphin expression in animals treated with chronic corticosterone and estradiol, based on observations that ER and GR can alter transcriptional activity via crosstalk at promoter response elements [48,49], including at the dynorphin promoter leading to increased dynorphin expression [50]. However, the current study showed a decrease in dynorphin mRNA expression in response to corticosterone, suggesting that upregulation of this inhibitory peptide is not likely to underlie the suppression in LH here.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Indeed, blocking dynorphin action with a kappaopioid receptor antagonist elicits an increase in LH pulse frequency [23,47] which is associated with increased multi-unit activity in the mediobasal hypothalamus [23]. We evaluated dynorphin expression in animals treated with chronic corticosterone and estradiol, based on observations that ER and GR can alter transcriptional activity via crosstalk at promoter response elements [48,49], including at the dynorphin promoter leading to increased dynorphin expression [50]. However, the current study showed a decrease in dynorphin mRNA expression in response to corticosterone, suggesting that upregulation of this inhibitory peptide is not likely to underlie the suppression in LH here.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It has been mentioned that SRC‐3 as an ERα cofactor is shared between breast cancer and ECa, and it is still unknown whether endometrial cancer‐specific ERα cofactors exist 27 . A previous study described the crosstalk between the glucocorticoid receptor (GR) and ERα in ECa, demonstrating that GR genomic binding sites are reprogrammed in ECa cells following treatment with E2 and dexamethasone (Dex), in which more GR were recruited to the sites normally bound by ERα to promote ECa progression 30 . Therefore, modulation of ERα‐induced transcriptional activation would be crucial for ECa.…”
Section: Discussionmentioning
confidence: 99%
“…Even though SHR-regulated transcription was initially studied as single receptor events, mediated by SHR homodimers [35], it is becoming evident that SHR crosstalk with each other and frequently co-regulate gene expression [34]. ER/GR crosstalk was extensively studied in hormone-dependent tissues such as uterus and breast, and in hormone-dependent cancers [34,[36][37][38]. Even though there has been a perception in the literature that GR and ER effects on gene expression are frequently reciprocal, careful literature analysis revealed that GR/ ER interactions are much more complex and cell and gene context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there has been a perception in the literature that GR and ER effects on gene expression are frequently reciprocal, careful literature analysis revealed that GR/ ER interactions are much more complex and cell and gene context-dependent. Indeed, there is an extensive overlap in ER and GR chromatin binding; both hormones induce global reprogramming of chromatin landscape that affects DNA accessibly for both receptors [36,38]. Moreover, upon co-activation, increased GR chromatin binding was observed at ER response elements, and at the same time, ER was associated with GR response elements, suggesting that ER and GR interact in a complex [34,36,38].…”
Section: Discussionmentioning
confidence: 99%